In vitro branched chain amino acid oxidation by porcine mammary tissue - B T Richert; Robert D Goodband; Michael D Tokach; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1995)
Mammary secretory tissue from six (three each of parity 1 and 2) lactating sows (d 10 to 17 of lactation) was obtained via biopsy for in vitro incubation to determine CO2 production fr01TI individual branched chain amino acids. Carbon dioxide production levels as percentages of the 14C-labeled amino acid metabolized by the mammary tissue were 2.57, 1.86, and 4.07% for isoleucine, leucine, and valine, respectively (P<.03). These results indicate that, in the lactating sow mammary gland, valine has the greatest oxidation rate of the branched chain amino acids.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Mammary gland; Sows; Isoleucine; Leucine; Valine